2018
DOI: 10.3389/fneur.2018.00900
|View full text |Cite
|
Sign up to set email alerts
|

Noisy Galvanic Vestibular Stimulation Sustainably Improves Posture in Bilateral Vestibulopathy

Abstract: Patients with bilateral vestibulopathy (BV) suffer from persistent postural imbalance, leading to a marked decrease in quality of life and a higher risk of falls. However, so far, the effective treatments for BV are very limited. We examined whether long-term noisy galvanic vestibular stimulation (nGVS) keeps improving body balance after the cessation of the stimulus in BV patients. Thirteen BV patients received nGVS for 30 min with a lower intensity than the intensity at which they feel any cutaneous sensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 38 publications
5
87
1
Order By: Relevance
“…However, amplitude is just one parameter of the stimulation signal to consider. Different groups have used frequency ranges of 0.02 to 10 Hz [13,18], 0.1 to 10 Hz [46], 0 to 30 Hz [20][21][22]24], which is similar to the present study, and even 0.1 to 640 Hz [16]. At this point, the optimal stimulation frequency range is unknown.…”
Section: Measure-interactions Threshold X Balance Threshold X Stimulasupporting
confidence: 73%
See 1 more Smart Citation
“…However, amplitude is just one parameter of the stimulation signal to consider. Different groups have used frequency ranges of 0.02 to 10 Hz [13,18], 0.1 to 10 Hz [46], 0 to 30 Hz [20][21][22]24], which is similar to the present study, and even 0.1 to 640 Hz [16]. At this point, the optimal stimulation frequency range is unknown.…”
Section: Measure-interactions Threshold X Balance Threshold X Stimulasupporting
confidence: 73%
“…Recently, several groups of researchers have demonstrated that the application of subthreshold stochastic vestibular stimulation (SVS), also known as noisy galvanic vestibular stimulation, is associated with improved balance control during standing and changes in walking patterns [13][14][15][16][17][18][19][20]. For example, SVS results in reduced postural sway length and velocity during eyes-open quiet standing in young and older adults [15,16] and during eyes-closed quiet standing in patients with bilateral vestibulopathy [13,17]. In addition, others found increased gait speed and changes in stride measures with SVS during treadmill and overground walking in healthy adults and patients with bilateral vestibulopathy [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The present study revealed that the vestibular system is involved in the development of obesity and its influences on glucose metabolism induced by energy excess in mice. A previous study showed that a noisy galvanic vestibular stimulation (nGVS), an imperceptible level of GVS, improves balance in patients with bilateral vestibulopathy [44]. Moreover, nGVS ameliorates autonomic nervous and motor functions in patients with central neurodegenerative disorders [45].…”
Section: Discussionmentioning
confidence: 99%
“…No commercial or financial conflicts of interest were disclosed in any of these studies. Journal of neurology (Q1) 12 Adults (6 female), age unspecified 2 complete BVD 10 partial BVD [28] Biological Cybernetics (Q1) 9 Adults (6 female), mean age =22 years Healthy [42] Frontiers in neurology (Q1) 13 Adults (5 female), mean age =63.1 ± 4.0 years BVD [37] Frontiers in neurology (Q1) 1 Adult (female), age =21 years Complete BVD and bilateral hearing loss [47] Frontiers in neurology (Q1) 4 Adults (2 female), mean age =58.8 years BVD Application technique was very similar in all studies. All stimulation was delivered bilaterally to electrodes placed on the mastoid processes behind each ear.…”
Section: Galvanic Vestibular Stimulation (Gvs)mentioning
confidence: 99%
“…This required a two-legged stance task in which the centre of pressure (COP) was measured and any changes in the following three parameters were recorded: COP velocity, COP envelopment area and the root mean square (RMS) of the COP. The task was performed with eyes closed in 2/8 cases to minimise visual contribution to balance [25,42]. Peterka et al [26] constrained subjects to sway as a 'single-link inverted pendulum', only allowing sway rotation around a single-axis located at ankle level.…”
Section: Galvanic Vestibular Stimulation (Gvs)mentioning
confidence: 99%